The upshot of cybercrime and brand trust on customer purchase intention of e-commerce - Made Srinitha Millinia Utami (Review of Management, Accounting, and Business Studies, 2021)
The rapid growth of digital marketing activities encourages the growth of e-commerce in line with the increase in internet users. The increase in the growth of E-Commerce is in line with the increasing number of cybercrime cases that occur. The phenomenon obtained in this study is that trust in brands encourages consumers' intentions to make purchases online even though it is accompanied by an increase in cybercrime cases. Therefore, this study aims to determine the phenomenon that occurs by examining the factors of cybercrime and brand trust toward customer purchase intention. The targeted respondents are e-commerce users with an age range of 18-35 years who live in Bali. The instrument used to obtain data in this study was the distribution of questionnaires conducted online with a five-point Likert scale. From the results of distributing the questionnaire, the researcher used 100 data to describe the population. Through the analysis data of PLS-SEM using SmartPLS 3.0 software, the results were obtained to state that all variables have a positive and significant effect.